Financial Performance of Insurance Firms. Does Leverage and Liquidity Matter? Evidence from Kenya - Kamau, Alex Maina; Olweny, Tobias; Muturi, Willy Mwangi (Eastern Journal of Economics and Finance, 2021)
The purpose of this study was to investigate the influence of firm attributes on the financial performance of insurance firms in Kenya. The study was anchored on trade off theory. The research philosophy adopted was positivism while the correlation research design was adopted. The study used secondary data which was collected using data collection sheet from Insurance Regulatory Authority (IRA), Association of Kenya Insurers (AKI) and individual firms’ websites. The target population of the study was 52 insurers that operated in Kenya for the ten years (2010-2018). The unbalanced panel data was analyzed using Random and Fixed effect model where Hausman test was used to establish to test the hypothesis. The study found that leverage and liquidity had a significant negative effect on financial performance of insurance firms in Kenya. The study recommends that insurance firms to embrace feasible financial leveraging strategies that can boost firm profitability. Also, they need to conduct effective liquidity management to maximize the value of the company and its financial performance.